Revisión de las Tecnologías y Aplicaciones del Habla Sub-vocal - Ramos Sandoval, Olga Lucia; Gamma Melo, Erika Nathalia; Amaya Hurtado, Dario (Ingeniería, 2015)
This paper presents a review of the main applicative and methodological approaches that have been developed in recent years for sub-vocal speech or silent language. The sub-vocal speech can be defined as the identification and characterization of bioelectric signals that control the vocal tract, when is not produced sound production by the caller. The first section makes a deep review of methods for detecting silent language. In the second part are evaluated the technologies implemented in recent years, followed by a review of the main applications of this type of speech and finally present a broad comparison between jobs that have been developed in industry and academic applications.